Early engagement with First Nations in British Columbia, Canada: a case study for assessing the feasibility of geological carbon storage - K. Steinthorsdottir; S. Pete; G. M. Dipple; R. Truman; S. Ó. Snæbjörnsdóttir (Geoscience Communication)
This work describes early engagement with 21 First Nations or alliances, which represent 41 Nations, in British Columbia, Canada. Geological researchers conducted this work as a case study to assess the feasibility of carbon storage in serpentinite rocks. The priorities for engagement were to inform people about the project idea and its implications, get consent for geological fieldwork, have a discussion, and start building relationships before discussing any future development plans. Aside from the geology and logistics of a site for a carbon storage project, the permitting and acceptance by the local community and the traditional lands' rights holders are needed for a successful project.